Studi tentang Pemahaman ASN Dinas Lingkungan Hidup dan Pelaku usaha terhadap Peraturan Pemerintah Nomor 22 Tahun 2021 Tentang Perlindungan dan Pengelolaan Lingkungan Hidup di Kabupaten Banyuasin - Muhammad Izhar (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Izhar M. 2021. Study on the understanding of civil servants of the office of environment and business actors on the government regulation number 22 of 2021 concerning environmental protection and management in Banyuasin District. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 811-815. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). After the issuance of the Law 11 of 2020 concerning Job Creation and its derivative regulations, the paradigm of licensing arrangements, especially environmental permits, underwent a significant change. These changes include those in the nomenclature of environmental permits to environmental approvals and changes to environmental management and protection permits to technical approvals. The lack of understanding of this regulation by ASN (civil servant) in the Office of Environment of Banyuasin District has caused confusion and concern for business actors in managing environmental permits. This study aimed to find out the level of understanding of ASN of the Office of Environment and Business Actors in Banyuasin District regarding the application of Government Regulation No. 22 of 2021 which resulted in non-optimal services in the management of environmental permits The method was random by conducting interviews and questionnaires to 10 ASN and 20 business actors in Banyuasin District. The results of this study showed that ASN's understanding of this regulation reached almost 50 percent and that of business actors reached 80 percent. In conclusion, there was still a very minimal understanding of ASN and Business Actors on the Implementation of Government Regulation Number 22 of 2021. It is necessary to carry out Socialization and Technical Guidance to improve understanding of Government Regulation Number 22 of 2021.